Incorporation of umiray agta foragers into the stratified social support network of a small community in the Philippines - Byers, Thomas Roy (Ann Arbor Michigan UMI Company, 1999)
"This dissertation describes the social organization of indigenous Umiray Agta-speaking people and their migrant neighbors in Tamala, Quezon, Philippines. It does so by means of a quantitative network model of stratified social support developed by the author. In this model, reciprocal supportive relationships are most likely between households with similar socioeconomic characteristics. Nonreciprocated ties are most likely between households with dissimilar socioeconomic characteristics."--Abstract.
Thesis (Ph.D.)--State University of New York at Buffalo, 1998.
Keywords: Quezon (Philippines : Province); Aeta (Philippine people) -- Social aspects; Dumagat language (Umirey)